Systematization and Description of Arterial Vascularization of the Paleopallia Area on the Brain Surface of Chinchilla (Chinchilla lanigera) - Pacheco de Araújo, Ana Cristina; Campos, Rui (Acta Scientiae Veterinariae, 2020)
Background: Chinchilla (Chinchilla lanigera) is a small rodent that in recent years has been increasingly used as a laboratory animal by different researchers. Brain irrigation is the object of study by several authors, being chinchilla classified as a vertebrobasillary animal, that is, it does not depend on the internal carotid artery to originate its cerebral arterial vascularization. Thus, the objective of this study was to systematize and describe the branches of the rostral, middle and caudal cerebral arteries that vascularized the paleopallia area of the chinchilla. Materials, Methods & Results: Thirty Chinchilla lanigera brains were used in this study, 17 females and 13 adult males from farms in the municipalities of Viamão and Santa Maria in the state of Rio Grande do Sul, Brazil. The animals were heparinized, with 5000 IU / animal, and after 30 min were sacrificed with 8 mL / 2.5% sodium thiopental animal, both intraperitoneally. The thoracic cavity was opened, the cardiac apex sectioned and the aortic arch was cannulated through the left ventricle. The arterial system was flushed with 0.9% cooled saline, 100mL / animal and then filled with 603 latex stained red with specific dye. The skin was recessed and a bone window opened in the cranial vault. Thus the pieces were fixed in 20% formaldehyde for seven days and after this period, the brain with a cervical spinal cord segment was removed and ventral schematic drawings of all preparations were prepared. The Veterinary Anatomical Nomina (2017) was used to name the cerebral arteries and their branches and for the statistical analysis of the results, the percentage calculation was applied. Brain irrigation in the chinchilla was supplied by the basilar artery, which was formed by anastomosis of the terminal branches of the right and left vertebral arteries, in the most caudal portion of the oblong medulla. The paleopallia areas corresponded to the olfactory trine, lateral brain fossa, piriform lobe, bulb and olfactory peduncle, and the medial and lateral olfactory tracts. Irrigation of the chinchilla paleopallia area was supplied by central branches from the caudal, middle and rostral cerebral arteries, and by the central branches originating from the terminal branches of the basilar artery. Discussion: Justifying the discussion about the systematization and description of arterial vascularization of the paleopallia area of the chinchilla brain, it was compared to other species such as wild boar, nutria, rabbit and greasy of the field, because only in these animals were found references on the subject. . The central branches of the cerebral arteries were mainly responsible for the irrigation of the paleopallia areas of the chinchilla brain, as well as in the species already mentioned. Due to the variation of the types of arterial vascularization in each of these species, small differences were observed, and these central vessels may also be emitted from the rostral branch of the internal carotid artery, such as in the rabbit and fatty grapefruit, or from the brain carotid artery as in wildboar. Similarities between chinchilla and nutria were also observed, and these central branches may originate from the terminal branches of the basilar artery in both species.